2004
DOI: 10.1021/la049085y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanotubes and Microtubes:  Experimental Evidence for Unsymmetrical Monolayer Membrane Formation from Unsymmetrical Bolaamphiphiles

Abstract: Unsymmetrical bolaamphiphiles, ω-[N-β-d-glucopyranosylcarbamoyl]alkanoic acids, with even-numbered oligomethylene chains (12, 14, 16, 18, and 20 carbons) self-assembled in water to form lipid nano- and microtubes. The tubular assemblies were separated by centrifugation and examined by transmission electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy to study the molecular packing within the tubular membranes. The nanotubes encapsulated the staining reagent phosphotungstate, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
172
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 52 publications
(81 reference statements)
12
172
0
Order By: Relevance
“…The bending angle, estimated to be α~ 33°, a value which is comparable with the one that has been reported by Masuda et al, 58 suggests an interlayer packing in the ribbon plane , as shown in scheme in Figure 7. The close analysis of the full width at half These techniques probe through-space 1 H-1 H (< 5 Å) and 13 C-1 H proximities using the nuclear spin interactions (dipolar coupling).…”
Section: Resultssupporting
confidence: 87%
“…The bending angle, estimated to be α~ 33°, a value which is comparable with the one that has been reported by Masuda et al, 58 suggests an interlayer packing in the ribbon plane , as shown in scheme in Figure 7. The close analysis of the full width at half These techniques probe through-space 1 H-1 H (< 5 Å) and 13 C-1 H proximities using the nuclear spin interactions (dipolar coupling).…”
Section: Resultssupporting
confidence: 87%
“…If the considerations above can partially explain the consistency among our data, they cannot explain the difference in morphology between the G-C18:0 sample, forming infinite bilayer membranes, and a very similar compound extensively studied by Masuda et al 30 forming nanotubes. The major difference between the two molecules resides in the chemical nature of the linker between the glucopyranoside ring and the fatty acid: acetal group in G-C18:0 and a carbamoyl group in the case of Masuda's sample.…”
Section: Discussionmentioning
confidence: 47%
“…We have achieved for the first time the precise control of the inner diameters of selfassembled LNTs by newly designing wedge-shaped amphiphiles 1(n) (n ¼ 12, 13, 14, 16, 18, and 20) (Scheme 1). 48 Two terminal hydrophilic groups of different size glucopyranose and carboxylic acid headgroups were covalently linked to an oligomethylene spacer (carbon numbers ¼ 12À20). Self-assembled organic nanotubes from 1(14), 1(16), 1 (18), and 1 (20) possess inner diameters in the 17.7À22.2 nm range at intervals of $1.5 nm, with an increment of two carbons in the spacer chains (Fig.…”
Section: Asymmetric Organic Nanotubes With Different Inner and Outer mentioning
confidence: 99%
“…Detailed Xray analysis confirmed that the molecules pack in a parallel fashion to form an unsymmetrical monolayer membrane, leading to different inner and outer surfaces covered with carboxylic and sugar hydroxyl groups, respectively. 48,49 These asymmetric supramolecular nanotubes are promisingly applicable to fill nanomaterials or biomacromolecules selectively into their hollow cylinders. It is known that the molecular packing of wedge-shaped amphiphiles in a solid state would include totally four types of polymorphism, depending on two types of polymorph and polytype for each.…”
Section: Asymmetric Organic Nanotubes With Different Inner and Outer mentioning
confidence: 99%